Strategic Analysis of the 2014 Wounded Warrior Project Annual Alumni Survey A Way Forward - Cerully, Jennifer L. (RAND Corporation, 2015)
Wounded Warrior Project (WWP) provides support and raises awareness for service members and veterans who incurred physical or mental health conditions during service, as well as their families and caregivers. WWP provides members (known as Alumni) with programs that support engagement, mind, body, and economic empowerment. This report details physical health, mental health, and employment needs of WWP Alumni in the 2014 WWP Annual Alumni Survey.